Effects of Weight Loss Speed on Kidney Function Differ Depending on Body Mass Index in Nondiabetic Healthy People: A Prospective Cohort - Kanda, Eiichiro (PLoS One, 2015)
BACKGROUND: Obesity is associated with diabetes mellitus and cardiovascular diseases. However, it has been reported that weight loss is associated with incident chronic kidney disease (CKD) in healthy males. The purpose of this prospective cohort study is to investigate the effects of weight loss on kidney function in healthy people in terms of body mass index (BMI) and gender. METHODS: A total of 8447 nondiabetic healthy people were enrolled in the Saitama Cardiometabolic Disease and Organ Impairment Study, Japan. Relationships between estimated glomerular filtration rate (eGFR) change, BMI, and BMI change were evaluated using 3D-scatter plots with spline and generalized additive models (GAMs) adjusted for baseline characteristics. RESULTS: The subjects were stratified into four groups according to BMI. The mean±standard deviations for males and females were, respectively, 40.11±9.49, and 40.3±9.71 years for age and 76.39±17.72 and 71.49±18.4 ml/min/1.73m(2) for eGFR. GAMs showed that a decreasing BMI change (<-1 kg/m(2)/year) was associated with a decreasing eGFR change in males with high normal BMIs (22 kg/m(2)≤BMI<25 kg/m(2)). A decreasing BMI change (<-2 kg/m(2)/year) was associated with an increasing eGFR change in overweight males (25 kg/m(2)≤BMI). Among underweight females (BMI<18.5 kg/m(2)), decreasing BMI was observed with decreasing eGFR. CONCLUSIONS: These findings suggest that the benefit and risk of weight loss in relation to kidney function differs depending on BMI and weight loss speed, especially in males.